Self-education in the Qur'an: The Prohibition of “Iltifat” as a Model - slamet riyadi; Abdel Aty, Ahmed (Al-Himam, 2024)
Many stories in the Quran can be used as a guide in living life, in which educational values will always be relevant at any time, including the present. One is the "al-iltifat" contained in two verses in the Quran. This paper will discuss in depth the values contained in the prohibition of looking back in the Quran and complement it with hadiths. With a detailed discussion on this matter, it is hoped that it will be a valuable contribution to the world of education, especially self-education. The method used in writing this paper is the descriptive qualitative method, by collecting data from relevant reading materials and then analyzing it in depth using scholarly opinions. From the results of the analysis, it was found that there are two types of "al-iltifat" in the Quran, namely "al-iltifat al-wajh” and "al-iltifat al-qalb”. Moreover, the most important thing to note between the two is the second type, al-iltifat al-qalb. However, there are times when iltifat is permissible on condition that there is a syar'i excuse in it